Possibility of correction of cerebral blood flow disorders and central nervous system damage with citicoline in patients with coronary artery disease in combination with COVID-19 - V.Z. Netiazhenko; S.Ye. Mostovyi (Civic Union "Communicable Diseases Intensive Care Association", 2024)
ABSTRACT. The review describes some pathogenetic mechanisms of central nervous system lesions in patients with coronary artery disease in combination with coronavirus disease (COVID-19) and presents the current possibilities of their pharmacotherapy. The analysis of experimental and clinical trials has shown that the multifactorial effect of citicoline on the main pathogenic links of brain damage in COVID-19 and numerous positive clinical effects make it a promising drug in the treatment of patients with coronary artery disease in combination with COVID-19 and post-COVID syndrome.